Kepemimpinan Prosedural dalam Penguatan Soliditas Partai Golkar Kota Jambi pada Pilkada Serentak 2024 - Fitriani, Ica; Subekti, Dimas; Pasaribu, Ian (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The 2024 regional elections in Jambi City sparked internal conflict within the Golkar Party when the recommendations of the Regional Representative Council II did not align with the Central Executive Board's decision regarding the mayoral candidate. The tension was successfully resolved through the implementation of procedural leadership based on the party's statutes and regulations, as well as a tiered nomination mechanism. This study aims to understand the role of procedural leadership in restoring solidarity and maintaining organizational stability after a nomination conflict. Using a qualitative approach with case studies, the study collected data through in-depth interviews and documentation with informants selected through purposive and snowball sampling. Data analysis was conducted using the Miles & Huberman model through data reduction, presentation, and conclusion drawing. The results show that procedural mechanisms, the use of surveys, and the exemplary behavior of charismatic figures particularly the chair of the DPD IIplay an important role in alleviating cadre disappointment. This study confirms that procedural leadership is a key instrument in maintaining the solidarity of the Golkar Party and recommends strengthening internal communication and balancing surveys with regional aspirations.